2017
DOI: 10.1139/cjz-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prey size on reproduction among populations of Diamond-backed Watersnakes (Nerodia rhombifer)

Abstract: Mean prey size often varies across landscapes, resulting in predator populations having differing access to energetic resources. Shifts in resource quality are likely to cause differences in energy allocation of reproduction. Thus, additional energy intake may lead to (i) increased offspring size, (ii) increased numbers of offspring, (iii) increased relative proportion of energy allocated to reproduction, (iv) increased absolute amount of energy allocated to reproduction or (v) increased energy allocated to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…A similar situation has also been observed in some studies, where, when threatened by long-term predation, the lifespan of aphid Rhopalosiphum padi will decrease, but the fecundity rate will increase [54]. The increased number of offspring may allow the individual that is eaten by a predator to be compensated [55]. This suggests that in our studies, the resources or energy diverted from development by female B. dorsalis may be allocated to fecundity or anti-predation, or to both of them.…”
Section: Discussionsupporting
confidence: 80%
“…A similar situation has also been observed in some studies, where, when threatened by long-term predation, the lifespan of aphid Rhopalosiphum padi will decrease, but the fecundity rate will increase [54]. The increased number of offspring may allow the individual that is eaten by a predator to be compensated [55]. This suggests that in our studies, the resources or energy diverted from development by female B. dorsalis may be allocated to fecundity or anti-predation, or to both of them.…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, diamond-backed watersnakes (Nerodia rhombifer), a sh-specialist predator that naturally colonized these newly constructed farms, experienced highly variable prey sizes among populations. Over the last twelve years, studies have clearly demonstrated substantial differences in many aspects of the life-history of these snakes including adult body size that correlate with the average size of sh prey produced at each site (Korfel et Among the sh farm populations of watersnakes we have measured, there are strong differences in initial offspring size that also correlate with prey size consistent with patterns of adult size (Chamberlain et al 2017).…”
Section: Introductionmentioning
confidence: 59%
“…While faster growth rates may be an indirect consequence of larger initial body sizes among populations, it is still unclear if variation in initial body size among populations is the product of selective pressure of prey size on neonates or the non-adaptive result of increased maternal investment in populations where females reach larger body sizes. Female body size is strongly correlated with offspring size in this species (Chamberlain et al 2017). It is surprising that very little work has been done to understand the relationship between average prey size and average initial offspring size in snakes, given the fact that they are gape-limited predators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation